Peran Kualitas Pelayanan dalam Kepatuhan Wajib Pajak Orang Pribadi: Sosialisasi Pajak dan Sanksi Pajak - Herly Pujilestari; Mutiara Humairo; Amrie Firmansyah; Estralita Trisnawati (Fakultas Ekonomi, Universitas Negeri Jakarta, 2021)
This study aims to examine the effect of tax socialization and tax sanctions on individual taxpayer compliance. In addition, this study also includes service quality as a moderator in the relationship between tax socialization and taxpayer compliance and the relationship between tax sanctions and taxpayer compliance. This study data employs primary data sourced from a survey questionnaire given to respondents, namely doctors who have an independent income. Based on purposive sampling, this study found 66 respondents who have filled out a questionnaire survey, but the data that can be employed and meet the criteria of this study are 50 questionnaires. This study concludes that tax socialization and tax sanctions have a positive effect on taxpayer compliance. Meanwhile, service quality weakens the positive effect of tax socialization on tax compliance and strengthens the positive effect of tax sanctions on taxpayer compliance. This research indicates that the Indonesian Tax Authorities need to improve all types of services to taxpayers.